Exploring the relationship between perceived technology-assisted teacher support and technology-embedded scientific inquiry: the mediation effect of hardiness. Issue 8 (23rd May 2020) - Lin, Xiao-Fan; Tang, Dandan; Shen, Weipeng; Liang, Zhong-Mei; Tang, Yaner; Tsai, Chin-Chung
ABSTRACT: This study examines the correlations between perceived technology-assisted teacher support; student hardiness (i.e. individual commitment, challenge, and control); and technology-embedded scientific inquiry (TESI) using a mediational model approach. Data were gathered from the series of questionnaires administered to 1566 Chinese students with an average age of 11.5. Structural equation modelling (SEM) analysis results confirmed our assumption that when students perceived technology-assisted teacher support, this promoted their TESI hardiness, indirectly increasing their perceived TESI. Perceived technology-assisted teacher support and TESI were found to be positively correlated in this structural model. However, by including TESI hardiness in the mediational mechanism, its direct relationship with both perceived technology-assisted teacher support and perceived TESI was insignificant, while the mediating effects remained significant. Therefore, TESI hardiness is of considerable importance for delineating the relationship between perceived technology-assisted teacher support and perceived TESI. It was revealed that both the interpersonal variable (perceived technology-assisted teacher support) and the individual variable (TESI hardiness) are vital in determining the effectiveness of TESI. These findings enhance the understanding of and approach to the promotion of students' perception of scientific inquiry by emphasising the value of technology-assisted teacher support and hardiness.